The Criminal Responsibility of Narcotics Offenders with a Death Sentence (A Study of Decision Number 280/Pid.Sus/2025/PN. Tjk) - Jainah, Zainab Ompu; Saputra, Bari (The Future of Education Journal, 2026)
The crime of drug abuse and illicit trafficking is a serious crime that has far-reaching consequences, both for public health conditions, social stability, and the future of the nation's future generations. In order to combat this crime, Law Number 35 of 2009 concerning Narcotics regulates strict and severe criminal sanctions, including the possibility of imposing the death penalty on certain perpetrators. The application of the death penalty in narcotics cases has caused polemics among academics and legal practitioners. The issues raised are: how to implement criminal accountability through the application of the death penalty for perpetrators of narcotics crimes based on Decision Number 280/Pid.Sus/2025/PN Tjk and what factors are taken into consideration in applying the principle of proportionality in sentencing according to Decision Number 280/Pid.Sus/2025/PN Tjk. The research method uses a normative and empirical juridical approach. The normative juridical approach is taken through a literature study by examining relevant laws and regulations, doctrines, and legal literature. Meanwhile, the empirical approach is carried out by interviewing parties involved or directly understanding the case in order to obtain a factual picture regarding the application of the law in the field. The results of the study indicate that criminal responsibility for the perpetrator in Decision Number 280/Pid.Sus/2025/PN Tjk has fulfilled all elements of a crime as regulated in Article 114 paragraph (2) of Law Number 35 of 2009 concerning Narcotics. These elements include the existence of an unlawful act, the existence of an element of error in the form of intent (mens rea), the ability of the perpetrator to be held legally accountable, and the existence of a clear causal relationship between the act committed and the resulting consequences. The application of the death penalty in this case is based on the consideration that the amount of Class I narcotics not plants controlled and distributed by the defendant has exceeded the threshold stipulated in the provisions of legislation. The application of the principle of proportionality in sentencing by the judge not only considers the severity of the act committed, but also takes into account various factors inherent in the perpetrator. These factors include internal and external conditions, such as economic background, level of education, personality, social environment, and cultural influences that shape the perpetrator's behavior. The suggestion from this study is that the government and society must continue to increase efforts to prevent narcotics crimes. These efforts can be carried out through strengthening education, fostering morals and religious values, and increasing supervision of the social environment. With the existence of sustainable prevention measures and involving various elements of society.